Angular moments of the decay [lambda] 0b→[lambda] [mu] + [mu] − at low hadronic recoil - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; De Cian, Michel; Comerma-Montells, Albert; Gerick, David; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Kecke, Matthieu; Khanji, Basem; Leverington, Blake; et al. (Journal of high energy physics, 2018)
An analysis of the angular distribution of the decay Λ b 0 → Λμ+μ− is presented, using data collected with the LHCb detector between 2011 and 2016 and corresponding to an integrated luminosity of approximately 5 fb−1. Angular observables are determined using a moment analysis of the angular distribution at low hadronic recoil, corresponding to the dimuon invariant mass squared range 15 < q2 < 20 GeV2/c4. The full basis of observables is measured for the first time. The lepton-side, hadron-side and combined forward-backward asymmetries of the decay are determined to be AℓFB=−0.39±0.04(stat)±0.01(syst),AhFB=−0.30±0.05(stat)±0.02(syst),AℓhFB=+0.25±0.04(stat)±0.01(syst).AFBℓ=−0.39±0.04(stat)±0.01(syst),AFBh=−0.30±0.05(stat)±0.02(syst),AFBℓh=+0.25±0.04(stat)±0.01(syst). \begin{array}{l}{A}_{\mathrm{FB}}^{\ell }=-0.39\pm 0.04\left(\mathrm{stat}\right)\pm 0.01\left(\mathrm{syst}\right),\hfill \\ {}{A}_{\mathrm{FB}}^h=-0.30\pm 0.05\left(\mathrm{stat}\right)\pm 0.02\left(\mathrm{syst}\right),\hfill \\ {}{A}_{\mathrm{FB}}^{\ell h}=+0.25\pm 0.04\left(\mathrm{stat}\right)\pm 0.01\left(\mathrm{syst}\right).\hfill \end{array} The measurements are consistent with Standard Model predictions. Open image in new window
The LHCb collaboration: R. Aaij, P. d'Argent, S. Bachmann, S. Braun, A. Comerma-Montells, M. De Cian, D. Berninghoff, M. Dziewiecki, D. Gerick, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, R. Kopecna, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, A. Piucci, N. Skidmore, M. Stahl, S. Stemmle, J. van Tilburg, U. Uwer, A. Zhelezov [und weitere]
Im Titel werden "Lambda" und "mu" als griechischer Buchstabe dargestellt
Im Titel werden die Zeichen "+" und "-" hochgestellt
Im Titel sind "0" und "b" untereinander geschrieben: "0" hochgestellt, "b" tiefgestellt
Gesehen am 04.06.2019